2022
DOI: 10.3390/nu14040902
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Probiotics for Management and Improvement of Reproductive Eubiosis and Function

Abstract: Reproductive tract dysbiosis, due to the action of pathogens and/or unhealthy lifestyle, has been related to many reproductive diseases and disorders in mammalian species. Classically, such a problem has been confronted by the administration of antibiotics. Despite their effectiveness for controlling disease, treatments with antibiotics may negatively affect the fertility of males and females and, mainly, may induce antibiotic resistance. Accordingly, safer alternatives for maintaining reproductive system eubi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 96 publications
0
19
0
Order By: Relevance
“…As individual approaches, intravaginal administration of probiotics and vaginal microbiota transplantation have been recently reported in humans [40] and are expected to be applied to cows. The establishment of these treatments in cows has the potential to reduce the use of antimicrobial agents to treat uterine disease and contribute to the control of the increase in antibiotic-resistant bacteria [41]. Regarding the herd approaches, hygiene practices adapted to the housing style and appropriate feeding management are required.…”
Section: Discussionmentioning
confidence: 99%
“…As individual approaches, intravaginal administration of probiotics and vaginal microbiota transplantation have been recently reported in humans [40] and are expected to be applied to cows. The establishment of these treatments in cows has the potential to reduce the use of antimicrobial agents to treat uterine disease and contribute to the control of the increase in antibiotic-resistant bacteria [41]. Regarding the herd approaches, hygiene practices adapted to the housing style and appropriate feeding management are required.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with healthy women, infertile patients with chronic endometritis have lower vaginal microbial diversity and abundance, especially Lactobacillus, which determines the embryo implantation rate and pregnancy rate [ 179 181 ]. Therefore, many studies have begun to focus on increasing the abundance of Lactobacillus to improve pregnancy outcome in infertile patients, and probiotics have received more and more attention for their anti-inflammatory, immunomodulatory, and maintenance of healthy and safe reproductive system properties [ 182 ]. A study conducted by Kyono et al [ 183 ] showed that the simultaneous use of antibiotics and probiotic supplements could effectively establish Lactobacillus predominance in the endometrium of infertile women to a certain extent, which is of great significance for improving the microbial status of the endometrium.…”
Section: Methodsmentioning
confidence: 99%
“…Due to the success of probiotics in the gastrointestinal tract, researchers have begun to evaluate the use of probiotics for the reproductive tract. In humans, both orally consumed and vaginally delivered probiotics have been successful as an alternative or an addition to antibiotic regimens for treating bacterial dysbiosis in the reproductive tract (Vujic et al, 2013;Abbasi et al, 2021;Hashem and Gonzalez-Bulnes, 2022). These probiotics typically consist of Lactobacillus or Bifidobacterium species (Hashem and Gonzalez-Bulnes, 2022).…”
Section: Probiotics In the Reproductive Tractmentioning
confidence: 99%
“…In humans, both orally consumed and vaginally delivered probiotics have been successful as an alternative or an addition to antibiotic regimens for treating bacterial dysbiosis in the reproductive tract (Vujic et al, 2013;Abbasi et al, 2021;Hashem and Gonzalez-Bulnes, 2022). These probiotics typically consist of Lactobacillus or Bifidobacterium species (Hashem and Gonzalez-Bulnes, 2022). Lactobacillus is used to restore the community to a Lactobacillus dominated state (Vujic et al, 2013).…”
Section: Probiotics In the Reproductive Tractmentioning
confidence: 99%